An Extra Hour Wasted? Bar Closing Hours and Traffic Accidents in Norway - Colin P. Green; Lana Krehic (Institute of Labor Economics (IZA), 2020)
Driving under the influence of alcohol is a major cause of fatalities worldwide. There have been a range of legislative and policy interventions that aim to address this. Bar closing hours is one policy with clear implications for drink driving. Existing evidence, largely drawn from one-off policy changes in urban settings, reports mixed evidence that is difficult to generalise. We return to this issue using a setting, Norway, that is advantageous due to large temporal and regional variation in closing times, frequent changes in closing hours, and a lack of other confounding policy changes. We demonstrate an average zero effect of closing hours on traffic accidents that masks large variations in effects, especially in terms of population density, accident severity, and direction of change in closing hours. Our results suggest that estimates from single policy changes may be difficult to generalise, while demonstrating that closing hours have the potential to generate large effects on traffic accidents.
Keywords: I18; R41; 330; closing hours; alcohol policy; traffic accidents